Mullite Ceramics: Its Properties Structure and Synthesis - Juliana Anggono (Jurnal Teknik Mesin (Sinta 3), 2005)
Besides its importance for conventional ceramics, mullite has become a choice of material for advanced structural and functional ceramics due to its favourable properties. Some outstanding properties of mullite are low thermal expansion, low thermal conductivity, excellent creep resistance, high-temperature strength, and good chemical stability. The mechanism of mullite formation depends upon the method of combining the alumina- and silica-containing reactants. It is also related to the temperature at which the reaction leads to the formation of mullite (mullitisation temperature). Mullitisation temperatures have been reported to differ by up to several hundred degrees Celsius depending on the synthesis method used. The three synthesis methods used to prepare mullite are discussed in this paper together with an overview of mullite, its properties and the current application of mullite. Abstract in Bahasa Indonesia : Keramik mullite tidak hanya penting dalam penggunaan konvensional, tetapi juga sudah menjadi bahan pilihan untuk aplikasi struktural dan fungsional karena sifat-sifatnya yang menguntungkan. Beberapa keunggulan sifat mullite adalah sifat muai dan konduktivitas panasnya rendah, ketahanan mulur yang tinggi, kekuatan yang terjaga pada temperatur tinggi, dan sifat korosinya yang baik. Mekanisme pembentukan mullite bergantung pada bagaimana proses menggabungkan reaktan yang mengandung alumina dan silika. Mekanisme tersebut juga bergantung pada temperatur reaksi awal yang akan mengarah pada pembentukan mullite (mullitisation). Beberapa penelitian melaporkan terjadinya temperatur mullitisation yang bervariasi hingga beberapa ratus derajat Celsius bergantung pada proses sintesa yang digunakan. Artikel ini menjelaskan tiga proses sintesa yang menghasilkan mullite yang dibahas bersama dengan sifat-sifat dan aplikasi mullite saat ini. Kata kunci: mullite, mullitisation, fasa glassy, sol-gel, spray pyrolysis, chemical vapour deposition.